Are the Elderly Perceived as a Burden to Society? The Perspective of Family Caregivers in Belgium and Kenya: A Comparative Study. (March 2019) - Six, Stefaan; Musomi, Sophia; Deschepper, Reginald
Introduction: It is estimated that 70% to 80% of informal care for frail and disabled elders is provided by family caregivers (FCGs).Aim: To better understand how caregiving for the elderly has affected FCGs lives and to compare the perspective of these caregivers in Belgium and Kenya.Method: Semistructured interviews were undertaken with 15 FCGs in Kenya and 15 FCGs in Belgium. Interpretative phenomenological analysis was used to identify themes.Results: Themes discovered in the experience of family caregiving included profile of the care receiver, impact of caregiving on the FCG, cultural values and norms, challenges in caregiving, coping strategies and caregiver well-being.Discussion: FCGs in both Kenya and Belgium identified experiencing serious concerns. In Kenya, the lack of resources and formal structures play a more important role than in Belgium. Despite this difference, culture-specific views and norms are paramount to explaining the FCG experience in the two countries.